Art, Development and Peace Working with Adolescents Living in Internally Displaced People's Camps in Mindanao. (22nd May 2017) - Baú, Valentina
Abstract: Within a framework of Communication for Development in Peacebuilding, this article sheds light on the use of art forms such as puppetry and photography as communication channels among youth affected by conflict and displacement. The study presented here evaluates UNICEF Art for Development programme, which was carried out with adolescents living in transitory sites in the city of Zamboanga in 2015. Rather than focusing on the therapeutic effect of the activities, this investigation looks at their ability to provide adolescents living in the context of community‐based conflict—such as that of a displaced people's camp—with a safe space to participate and collaborate in art and media production to express themselves and communicate with one another. Copyright © 2017 John Wiley & Sons, Ltd.